Multi-Stage Control of Waste Heat Recovery from High Temperature Slags Based on Time Temperature Transformation Curves - Yongqi Sun; Zuotai Zhang; Lili Liu; Xidong Wang (Energies, 2014)
This paper presents a significant method and a basic idea of waste heat recovery from high temperature slags based on Time Temperature Transformation (TTT) curves. Three samples with a fixed CaO/SiO2 ratio of 1.05 and different levels of Al2O3 were designed and isothermal experiments were performed using a Single Hot Thermocouple Technique (SHTT). The TTT curves established through SHTT experiments described well the variation of slag properties during isothermal processes. In this study, we propose a multi-stage control method for waste heat recovery from high temperature slags, in which the whole temperature range from 1500 °C to 25 °C was divided into three regions, i.e., Liquid region, Crystallization region and Solid region, based on the TTT curves. Accordingly, we put forward an industrial prototype plant for the purpose of waste heat recovery and the potential of waste heat recovery was then calculated. The multi-stage control method provided not only a significant prototype, but also a basic idea to simultaneously extract high quality waste heat and obtain glassy phases on high temperature slags, which may fill the gap between slag properties and practical waste heat recovery processes.